Elastic wave propagation in parallel: the huygens' approach - Sabadell, Javier (Revista Matemática Complutense, 2002)
The use of parallel computers makes it feasible to simulate elastic waves throughout large heterogeneous structures, and new domain decomposition methods can be used to increase their ef- _ciency and decrease the computing time spent in the simula- tion. In this paper we introduce a simple parallel algorithm for the propagation of elastic waves in complex heterogeneous media after a _nite element discretization. This method performs more eÆciently than classic domain decomposition techniques based on substructuring (Schur complement methods) and iterative domain decomposition. Some numerical examples are shown, including an